2018
DOI: 10.1016/j.aninu.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotics and botanical extracts to improve ruminant production in the tropics: A review

Abstract: Ruminant production, especially in the tropics and developing countries suffers a setback when compared with the temperate and developed countries, which is attributable to the kinds of available feed resources in the region of production. In the tropics, ruminants are restricted to grazing on low-quality forages, crop residues and agro-industrial by-products with very little or no concentrate diets, which adversely affect the animals in exhibiting their full production potential. Considering this fact, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 69 publications
3
72
2
7
Order By: Relevance
“…The ruminal bacterial populations depend on sufficient nutrients or stimulants supply 38 . Yeast is a great supply to stimulate bacteria because it is enriched in essential substances 40 . Previous studies have confirmed that yeast could supply essential amino acids, vitamins, and minerals to increase the ruminal bacteria more than without yeast 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The ruminal bacterial populations depend on sufficient nutrients or stimulants supply 38 . Yeast is a great supply to stimulate bacteria because it is enriched in essential substances 40 . Previous studies have confirmed that yeast could supply essential amino acids, vitamins, and minerals to increase the ruminal bacteria more than without yeast 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that secondary metabolites of plants can decrease methanogenic archaea, deriving the hydrogen for propionate formation (Frankič et al 2009;Holtshausen et al 2009;Oskoueian et al 2013;Arowolo and He 2018) and considering the plants in the polyherbal and its metabolites and an increase in propionate and a reduction in methane was expected (Kamra et al 2006;Mirzaei and Venkatesh 2012), however results suggests that butyrate-producing bacteria were stimulated by an unknown mechanism; Butyrivibrio represent among 10-30 % of culturable rumen bacteria in ruminants; molecular studies have identified other novel bacteria which can produce butyrate (Kopečný et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast’s important roles include oxygen scavenging by reducing the amount of oxygen in the rumen and increasing the survival of other anaerobic microorganisms supplying essential nutrients such as mannooligo saccharide, protein or protein amino acid chelates, vitamins (B-complex), and minerals to other microorganisms upon cell lysis in the rumen; yeast can also stimulate the immune system in the hindgut [ 3 ]. These mechanisms affect animals by leading to maximum microbial population in the rumen, which increases their effectiveness in terms of their subsequent productivity [ 4 ]. Previous studies have confirmed that supplementation of S. cerevisiae as a direct feed can improve animal performance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%